Lexico-Semantic Innovations in the Texts of the Ukrainian Mass Media on Military Topics - Navalna, Maryna I.; Shynkaruk, Vasyl; Kostusiak, Nataliia M.; Prosianyk, Oksana; Chernobrov, Yuliia; Adamchuk, Nataliya (My University, 2023)
The article classifies lexical and semantic innovations in the texts of the Ukrainian mass media on military topics. The analyzed corpus of lexemes expanded the scope of use both in language practice and in the language of domestic Ukrainian mass media. During the research, lexemes of various partial linguistic affiliations, which are evidenced in the media information field during the period of the Russian- Ukrainian war, were comprehensively studied; the semantic nuances of language units are characterized, occasional formations are revealed, words and phrases in dynamics are considered, stylistic expressiveness in journalistic style is emphasized. In the article, for the study of lexical-semantic innovations in the language of the Ukrainian mass media, the observation method and the descriptive method are used as the main ones. At various stages of the study and classification of language units, the method of functional analysis was used to determine the stylistic load of lexical units. The source of the presented lexical material was modern Ukrainian mass media texts of both regional and all-Ukrainian information space. As evidenced by the collected mass media material of the period of the Russian-Ukrainian war (2022), the latest lexemes and well-known words with new meanings and fixed phrases that have acquired additional variants of meaning are widely used in the language of modern Ukrainian journalism. In the language of mass media, we record new verbs that are often formed from proper names, but mainly convey actions, processes, and states that are characteristic of the surnames of persons or the names of settlements. A tendency for journalists is traced - to use new nouns and occasional formations. Nouns in mass media texts often acquire new meanings that are understandable only from the context. Under the action of non-linguistic factors, a group of phrases was shaped which form new meanings and function as stable ones. Lexical-semantic innovations mostly give the language of the mass media a negative assessment: they convey contempt for the invaders and their politicians, emphasize their vulgarity and inability to resist the Ukrainian military and the people in general. Some lexemes name or characterize Ukrainian figures and soldiers for their courage, stability, and confidence in their behavior.
Keywords: innovations; lexical-semantic system; variants of meanings; language of Ukrainian mass media; military topics